OPTIMIZATION OF QRIS VIRTUAL PAYMENT TOOLS AS A SUPPORTER OF THE ISLAMIC ECONOMY FOR MUSLIM MSMES GO DIGITAL - May Shinta Retnowati (JASIE, 2023)
This study aims to analyze the benefits of using QRIS as a non-cash transaction tool for MSME players to realize MSMEs go digital. QRIS is a new innovation launched by Bank Indonesia in collaboration with the Indonesian Payment System Association which was launched on the 74th independence day of the Republic of Indonesia, namely August 17, 2019. This research uses a library approach. The results of this study show that the benefits of using QRIS have a major influence on the development of the Sharia economy, especially Muslim MSME players.